Peningkatan Keterampilan Mengemukakan Pendapat Peserta Didik Melalui Model Problem Terbuka (Open Ended) Pada Mata Pelajaran Pendidikan Kewarganegaraan - Muhammad Mona Adha; Dayu Rika Perdana; Nur Ardiansyah; Roy Kembar Habibi (Sekolah Tingi Keguruan dan Ilmu Pendidikan (STKIP) PGRI Tulungagung, 2021)
Schools not only teach students in knowledge but teach them how to have skills in opinion because this is very important for students. Many steps can be taken by educators to be able to improve the opinion skills of the students themselves. Thus, the learning process in the world of education today is faced with various choices of learning models. The existence of a learning model, demands the role of an educator to always innovate in the classroom. Educators must be able to choose a learning model because the model chosen will have a direct impact on students. This article aims to analyze how the open problem learning model can improve students' speaking skills. The method used in this paper is to use the approach to writing this article is a qualitative conceptual analysis. The results of this article discuss the concept of open problems in elementary schools and skills in expressing students' opinions through open problem models in low-grade PPKn subjects. Meanwhile, the recommendations of this article can target educators because educators have a central role in selecting and applying open problem learning models to students.